6
$\begingroup$

The equation is $x^2-4x=y^2-4y$ in the case where $x\ne y$. The answer is $x+y=4$.

I can start from $x+y=4$ and create the equation very easily, and I can substitute $x+4=y$ into the equation and show both sides are equal easily. I just don't get how I would find the answer if I didn't know it before hand, and all I had was the equation? Any advice?

$\endgroup$
  • $\begingroup$ I just realized, assuming that x and y aren't equal, then x must equal +/- (y-4) and y must equal +/- (x-4), otherwise there's no way x(x-4)=y (y-4). $\endgroup$ – Hockeyfan19 Nov 27 '17 at 2:11
  • $\begingroup$ Be weary of the line of reasoning; it’s fallacious. Just because $ab = cd$ and $a \neq b$, doesn’t mean $a = c$. That trick only works when we have something like $ab = 0$, whence we can conclude $a$ or $b$ is zero. See the most recent answer to this question for the right application of this idea. It’s subtle. $\endgroup$ – Bob Krueger Nov 28 '17 at 1:49
25
$\begingroup$

\begin{align} x^2 - 4x &= y^2 - 4y \\ x^2 - y^2 &= 4x - 4y \\ (x-y)(x+y) &= 4(x-y) \\ x+y &= 4\end{align} where dividing by $x-y$ is allowed since $x \neq y$.

$\endgroup$
  • 2
    $\begingroup$ It seems so obvious now, thanks for showing the way! I wasn't seeing it at all. $\endgroup$ – Hockeyfan19 Nov 26 '17 at 21:17
12
$\begingroup$

As an alternative, the solution that struck me first was completing the square in both $x$ and $y$. This is common when dealing with quadratics, especially once there are no $xy$ cross-terms. $$ x^2 - 4x = y^2 - 4y $$ $$ x^2 - 4x + 4 = y^2 - 4y + 4 $$ $$ (x-2)^2 = (y-2)^2 $$ This means that either $x-2 = y-2$ or $x-2 = -(y-2)$, which means either $x = y$ or $x+y = 4$, as desired.

$\endgroup$
  • $\begingroup$ I actually saw that I could complete the square when I was working on it. I missed that it would progress towards the solution though. Thanks for the alternative approach! $\endgroup$ – Hockeyfan19 Nov 27 '17 at 1:38
  • $\begingroup$ You're welcome. Look into quadratic forms and conic sections for more general problems of this type. $\endgroup$ – Bob Krueger Nov 27 '17 at 1:44
  • $\begingroup$ This is the way I first went, so +1 ;) $\endgroup$ – Lamar Latrell Nov 27 '17 at 4:37
7
$\begingroup$

Let $c$ be the common value of $x^2-4x$ and $y^2-4y$. Then $x$ and $y$ are both roots of the polynomial $t^2-4t-c$. Since we are assuming $x$ and $y$ are distinct, they are all of the roots, so $t^2-4t-c$ factors as $(t-x)(t-y)$. Since $(t-x)(t-y)$ expands to $t^2-(x+y)t+xy$, comparing the coefficients of $t$ gives $x+y=4$.

(Conversely, if $x+y=4$, then since $x$ and $y$ are both roots of $(t-x)(t-y)=t^2-(x+y)t+xy=t^2-4t+xy$, $x^2-4x$ and $y^2-4y$ are both equal to $-xy$.)

$\endgroup$
  • $\begingroup$ Very interesting approach, but where did the -4t come from in your polynomial? $\endgroup$ – Hockeyfan19 Nov 27 '17 at 2:04
  • $\begingroup$ I'm not sure what you mean. Since $x^2-4x=c$, $x^2-4x-c=0$, and similarly for $y$. So $x$ and $y$ are roots of $t^2-4t-c$. $\endgroup$ – Eric Wofsey Nov 27 '17 at 2:32
  • $\begingroup$ Okay so it comes from the original equation, I see now $\endgroup$ – Hockeyfan19 Nov 27 '17 at 2:43
  • $\begingroup$ And you're using the t for clarities sake I think? $\endgroup$ – Hockeyfan19 Nov 27 '17 at 2:45
2
$\begingroup$

Write $x+y=d$. Then we have $y=d-x$ and so: $$(d-x)^2-4(d-x) = x^2-4x$$ so $$d^2-2dx-4d =-8x$$thus $$d(d-2x)-4(d-2x)=0$$ so $$(d-2x)(d-4)=0$$ If $d=2x$ we get $x=y$ which is impossible. So $d=4$ and we have $x+y=4$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.